[Adverstisement for Caroni Ltd's Puncheon Rum] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Advertisement of one of Caroni Limited's Stallion, a brand of puncheon rum sold by Caroni (1975) Ltd.
Cataloger's title
Keywords: Advertising—Alcoholic beverages -- Trinidad and Tobago; Caroni (1975) Limtied